Susceptibility to type 1 diabetes conferred by the PTPN22 C1858T polymorphism in the Spanish population - Figueredo M Ángeles; Fernández-Arquero Miguel; de la Calle Hermenegildo; Martínez Alfonso; Santiago Jose; de la Concha Emilio G; Urcelay Elena (BMC, 2007)
Abstract Background The protein tyrosine phosphatase N22 gene (PTPN22) encodes a lymphoid-specific phosphatase (LYP) which is an important downregulator of T cell activation. A PTPN22 polymorphism, C1858T, was found associated with type 1 diabetes (T1D) in different Caucasian populations. In this study, we aimed at confirming the role of this variant in T1D predisposition in the Spanish population. Methods A case-control was performed with 316 Spanish white T1D patients consecutively recruited and 554 healthy controls, all of them from the Madrid area. The PTPN22 C1858T SNP was genotyped in both patients and controls using a TaqMan Assay in a 7900 HT Fast Real-Time PCR System. Results We replicated for the first time in a Spanish population the association of the 1858T allele with an increased risk for developing T1D [carriers of allele T vs. CC: OR (95%) = 1.73 (1.17-2.54); p = 0.004]. Furthermore, this allele showed a significant association in female patients with diabetes onset before age 16 years [carriers of allele T vs. CC: OR (95%) = 2.95 (1.45-6.01), female patients vs female controls p = 0.0009]. No other association in specific subgroups stratified for gender, HLA susceptibility or age at onset were observed. Conclusion Our results provide evidence that the PTPN22 1858T allele is a T1D susceptibility factor also in the Spanish population and it might play a different role in susceptibility to T1D according to gender in early-onset T1D patients.